Teledentistry—Dental students’ preparedness and patients’ experiences - Swarna Math; Janice Diong Li Nga; Huey Fen Lim; Maryam Amin; Camila Pacheco-Pereira (PLoS ONE, 2025)
Objectives To explore dental students’ preparedness, experiences and confidence levels in utilizing teledentistry (TD) for patient care during the COVID-19 pandemic and to determine the dental needs and experiences of patients receiving treatment from dental students through TD. Methods Two online surveys were administered through Google Forms, incorporating both five-point Likert scales and open-ended questions alone for the student questionnaire. The patient questionnaire, available in English and Mandarin, was distributed during or after teleconsultations. Descriptive statistics were used to summarise the data. Results Out of 125 students, 88% (N = 110) were contacted by 318 patients. Of them, 79.1% reported no telecommunication problems, 91.8% faced no language barriers, and 87.2% encountered no technological barriers. Most students (67.3%) agreed they would need further training in TD. Low confidence levels were observed among 26.3% of students in managing crowns and bridges and among 18.2% of students in managing mucosal conditions. From the patient perspective, 76.4% contacted the students via WhatsApp Messages and 21.0% used the Voice Call mode. About 44.0% of patients enquired about the next available appointment. Their most common concern was tooth pain (15.1%) followed by denture problems (9.1%), chipped fillings (6.6%), and crowns and bridge problems (6.3%). Overall, 82% patients reported effective communication during teleconsultation, 85% were satisfied with the questioning process, and expressed satisfaction with the diagnoses provided. However, 10% of patients chose to ignore their concerns, and 5% sought assistance from medical practitioners. Conclusion Most dental students were confident in addressing patient concerns but recognized the need for additional training for managing complex cases. Both students and patients reported positive experiences with TD, including effective communication and satisfaction. These findings highlight the importance of integrating TD training into dental curricula, addressing technical and privacy concerns, and improving patient education for secure and effective TD use in routine care.